Italian communist dissidence and transnational Trotskyism towards the Fourth International (1928-1938) - Mastrolillo, Gabriele (Marx and Marxisms., 2026)
Following his expulsion from the Soviet Union in 1929, Leon Trotsky promoted the birth of an International Anti-Stalinist Communist movement which considered itself in opposition to the Communist International (Comintern). However, since 1933, it began to regard itself as an independent transnational organization in direct competition with the Comintern. Italian Communist Dissidence and Transnational Trotskyism towards the Fourth International (1928-1938) draws from wide-ranging primary and secondary sources, most of which are unpublished, to tell the fascinating unexplored story of the relations between the Italian communist dissidence (Trotskyist and Bordigists), Trotsky, and the International Secretariat (IS), the leading structure of the Trotskyist movement in the 1930s. It focuses on the role played by the two most notable executives of Italian dissident communism, Alfonso Leonetti and Pietro Tresso, who performed key roles inside the IS; consequently, the study of their activity gives us the possibility of following the development of Transnational Trotskyism in the 1930s until the establishment of the Fourth International. Written for scholars of Italian and International Communism, this book will also appeal to those interested in learning how Italian Trotskyism contributed to the building of a global alternative to Stalinism.